A Physical Therapy–Based Outpatient Rehabilitation Program for Older Adults With Heart Failure: A Retrospective Analysis of Changes in Functional Performance. Issue 1 (January 2016) - Pastva, Amy M.; Lowers, Sean; Sibley, Alexander B.; Lian, Huizi; Pierson, Dana; Turner, Elizabeth L.; Patel, Mahesh
Abstract : Purpose: It is recommended that individuals with heart failure (HF) participate in supervised exercise programs, given lower incidences of adverse events compared with independently initiated and progressed exercise. The purpose of this study was to retrospectively evaluate the effect of a physical therapy (PT)-based outpatient rehabilitation program on the functional performance of older adults diagnosed with HF. Methods: Fifty-four adults (55 years or greater) completed a 24-session exercise and educational program. The primary outcome was change in 6-minute walk distance (6MWD). Secondary outcomes included change in dyspnea on exertion (DOE), rate of perceived exertion (RPE), number of rest breaks, and use of an assistive device during the 6MWD assessment along with 6-minute walk work (6MWORK), body weight, body mass index (BMI), and average wattage during recumbent cycling. Results: Six-minute walk distance increased 30.2% or 109.5 m from baseline. Although there was no change in assistive device, rest breaks and DOE and RPE values during the 6MWD assessment decreased by 22%, −1.4 units, and −1.2 units, respectively. Average wattage on the cycle increased by 15.0, and 6MWORK increased by 29.7% or 10, 678.6 kg·m. Weight and BMI did not change, but BMI did influence the absolute change in 6MWD. Conclusions: The PT-based outpatient rehabilitation program improved the functional performance of older adults diagnosed with HF. Further investigation is needed to explore the specific contributions the program and PT interventions have on clinical and patient-centered outcomes (ie, readmissions, survival, function, quality of life).